PRACTICAL IMMUNOPATHOLOGY OF THE SKIN - IVAN DAMJANOV, MD (2002)
Practical Immunopathology of the Skinbegins with a discussion of the science behind immunopathology and an explanation of the immunoperoxidase technique and its most frequently used modifications. Issues of tissue preparation, antigen retrieval techniques, and pitfalls that occur in the laboratory will be addressed.